The Role of Information and Communication Technology to Indonesian Craft Export - Nora Muhtasib (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2022)
Indonesian handicraft products are potential export products that can survive amid sluggish Indonesian non-oil and gas exports. Indonesian handicraft exports today are also influenced by the development of information and communication technology. This study aims to determine the effect of information and communication technology on Indonesian handicraft exports during 2010-2019. The method used is a gravity model approach for panel data. However, due to heteroscedasticity problems and errors that are not normally distributed, the method was developed into a random effect quantile regression model. The data used is panel data consisting of 10 main destination countries for Indonesian handicraft exports during the 2010-2019 period. The results indicate that mobile broadband and mobile cellular users of export destination countries and individual Indonesian internet usage, significantly affects Indonesian handicraft exports on the middle and upper quantiles data. However, in the lower quantile, Indonesia's individual internet usage does not significantly affect Indonesian handicraft exports. Increasing penetration of Indonesia's internet usage for handicraft products marketing can be directed at countries belonging to the lower quantiles, such as the United Kingdom and The United Arab Emirates.